PENGARUH KOMPETENSI SUMBER DAYA MANUSIA (SDM), MOTIVASI KERJA, DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI STIE SAKTI ALAM KERINCI KOTA SUNGAI PENUH - Kurnia Sari, Rizka; Afriyeni, Afriyeni (Jurnal Ekonomi Sakti, 2026)
This study aims to analyze the influence of competence, motivation, and leadership style on employee performance. This study uses a quantitative approach with data collection techniques through questionnaires to 50 respondents. The analysis method used is multiple linear regression with the help of statistical tests. The results of the study indicate that partially competence has a significant effect on employee performance with a calculated t value of 2.87> t table 2.01 and a significance value of 0.006 <0.05. Motivation also has a significant effect with a calculated t value of 3.12> 2.01 and a significance of 0.003 <0.05. Leadership style has a significant effect with a calculated t value of 2.65> 2.01 and a significance of 0.011 <0.05. Simultaneously, competence, motivation, and leadership style have a significant effect on employee performance with a calculated F value of 18.45> F table 2.80 and a significance of 0.000 <0.05. The coefficient of determination (R²) of 0.68 indicates that 68% of the variation in employee performance can be explained by these three variables, while the remaining 32% is influenced by factors outside the study. The conclusion of this study indicates that competence, motivation, and leadership style have a positive and significant influence on employee performance, thus requiring primary attention in efforts to improve organizational performance.